Comparison of The Melatonin Preconditioning Efficacy between Bone Marrow and Adipose-Derived Mesenchymal Stem Cells - Rafat, Ali; Mohammadi Roushandeh, Amaneh; Alizadeh, Akram; Hashemi-Firouzi, Nasrin; Golipoor, Zoleikha (Cell journal (Yakhteh), 2019)
Mesenchymal stem cells (MSC) from various sources have the potentials to positively affect regenerative medicine. Furthermore, pre-conditioning strategies with different agents could improve the efficacy of cell therapy. This study compares the effects of an anti-inflammatory and antioxidant agent, melatonin, on protection of bone marrow-derived MSCs (BMSCs) and adipose tissue-derived MSCs (ADSCs). In this experimental study, rat BMSCs and ADSCs were isolated and expanded. Pre-conditioning was performed with 5 μM melatonin for 24 hours. Cell proliferation and viability were detected by MTT assay. Expression of BAX, BCL2, melatonin receptors and osteocalcin genes were evaluated by reverse transcriptase-polymerase chain reaction (RT-PCR). Also, apoptosis was detected with tunnel assay. Osteogenic differentiation was analyzed using alizarin red staining. No significant increase was found in cell viability between BMSCs and ADSCs after melatonin preconditioning. Following melatonin preconditioning, BAX expression was significantly down-regulated in both ADSCs and BMSCs (P<0.05), with the difference being more significant in ADSCs compared to BMSCs. BCL2 expression was increased significantly in both cell types after preconditioning. Metalothionine 1 and Metalothionine 2 were both upregulated significantly in the two cell types (P<0.05). Melatonin increased osteogenesis capability through increasing osteocalcin expression. However, expression of osteocalcin in BMSCs before and after preconditioning was higher than that in ADSCs. On the other hand, melatonin expression in ADSCs was in higher levels than in BMSCs. Melatonin also improved alizarin red concentration significantly in both BMSCs and ADSCs (P<0.05). Alizarin red staining severity increased significantly in ADSCs after preconditioning compared to BMSCs (P<0.05). Here we have shown that the effects of preconditioning on melatonin expression in ADSCs are higher than those in BMSCs. These findings could be used in adoption of a proper preconditioning protocol based on the sources of MSCs in specific clinical applications, especially in bone regeneration.